Graphene/semicrystalline-carbon derived from amylose films for supercapacitor application - M Deraman; N E S Sazali; M F Y M Hanappi; N S M Tajuddin; E Hamdan; M Suleman; M A R Othman; R Omar; M A Hashim; N H Basri; N S M Nor; B N M Dolah; et al. (IOP Publishing Ltd, 2016)
Graphene/semicrystalline-carbon in the form of carbon flakes is produced by carbonization up to 600, 700, 800, 900 and 1000°C, respectively, of the amylose films prepared by a casting method on copper foil substrate. The carbon flakes are characterized by X-ray diffraction (XRD) method to determine their microcrystallite interlayer spacing, width and stack-height; and Raman spectroscopy (RS) method to obtain structural information from the D-, D2- and G-bands peak-intensities. The XRD results show that increase in carbonization temperature lead to ~(1-3 %), ~85 % and ~30 %increase in the microcrystallites interlayer spacing, width and stack-height, respectively, indicating that a larger growth of microcrytallite of carbon flakes occurs in the direction parallel to (001) plane or film planar surface. The specific surface area of carbon flakes estimated from the XRD results in decreases from ~4400 to ~3400 m2/g, corresponding to the specific capacitance between ~500 to ~400 F/g, which are well within the range of specific capacitance for typical electrodes carbon for supercapacitor application. The RS results show that the multilayer graphene co-exist with semicrystalline-carbon within the carbon flakes, with the multilayer graphene relative quantities increase with increasing carbonization temperature.